Drug resistance and tropism as markers of the dynamics of HIV-1 DNA quasispecies in blood cells of heavily pretreated patients who achieved sustained virological suppression. (16th December 2015) - Gantner, Pierre; Morand-Joubert, Laurence; Sueur, Charlotte; Raffi, François; Fagard, Catherine; Lascoux-Combe, Caroline; Salmon, Dominique; Amiel, Corinne; Lambert-Niclot, Sidonie; Fofana, Djeneba Bocar; Viard, Jean-Paul; Fafi-Kremer, Samira; et al.
Abstract: Objectives: The objective of this study was to address the dynamics of archived resistant quasispecies in cell-associated HIV-1 DNA over time in heavily ART-experienced patients with currently suppressed plasma HIV-1 RNA. Methods: Longitudinal ultra-deep sequencing (UDS) analysis of reverse transcriptase, protease and V3 Env regions was performed on blood-cell-associated HIV-1 DNA samples. Drug-resistance-associated mutations (DRAMs) and tropism were interpreted using the ANRS and Geno2Pheno algorithms. We analysed frozen blood cells from patients enrolled in the INNOVE and ANRS 123 ETOILE studies who achieved sustained viral suppression after salvage optimized ART (SOT). Results: Samples were available at baseline and 6 and ≥12 months after SOT initiation in 10 patients. V3 loop sequences displayed wide intra-individual dynamics over time. Viral variants harbouring DRAMs exhibited three non-exclusive scenarios. First, when SOT exerted the same selective pressure as previous failing regimens, some viral quasispecies still harboured the same DRAMs at the same level as at the time of virological failure. Thus, as DRAMs were mostly associated with the same viral variant, variants with a complete resistance pattern remained archived. Second, some viral variants harbouring DRAMs were no longer detected over time when SOT consisted of new antiretroviral classes or had resistance profiles distinct from those of previous failing regimens. Third, variants with new DRAMs associated with SOT emerged in blood cells during follow-up despite sustained virological control. Conclusions: Using longitudinal UDS analysis and focusing on DRAMs and tropism as markers, we demonstrated that, despite sustained virological control, archived HIV-1 DNA quasispecies continued to evolve.